2020
DOI: 10.3390/w12092435
|View full text |Cite
|
Sign up to set email alerts
|

Ice Regime of the Kozłowa Góra Reservoir (Southern Poland) as an Indicator of Changes of the Thermal Conditions of Ambient Air

Abstract: Ice phenomena are construed as the occurrence of ice in water irrespective of its structure, form, and duration. One of the most frequently discussed research problems is the possibility of using long-term ice phenology as an indicator of changes of the thermal conditions of ambient air. The study used correlation analysis and regression models in order to determine changes in the parameters studied over time. In order to compare the ice regime of the study reservoir and other lakes in the region, discriminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 64 publications
0
14
0
4
Order By: Relevance
“…While analysing the course of the change in the ice cover of Jagodne Lake (north‐eastern Poland), Ptak et al (2019a,b,c) concluded that the ice cover duration is getting shorter and shorter (5 days/decade on average) and the ice thickness is getting thinner (2 cm/decade on average). The Kozłowa Góra in the south of Poland was characterised by a decrease in the number of days with ice cover (by 8.6 days/decade), and a decrease in the maximum thickness of lake ice – on average by 2 cm/decade (Solarski & Rzętała, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While analysing the course of the change in the ice cover of Jagodne Lake (north‐eastern Poland), Ptak et al (2019a,b,c) concluded that the ice cover duration is getting shorter and shorter (5 days/decade on average) and the ice thickness is getting thinner (2 cm/decade on average). The Kozłowa Góra in the south of Poland was characterised by a decrease in the number of days with ice cover (by 8.6 days/decade), and a decrease in the maximum thickness of lake ice – on average by 2 cm/decade (Solarski & Rzętała, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The turbulent transfer coefficients at the air-ice interface were calculated from Equations (7) and (8)(9)(10). The estimation of the bulk Richardson number was limited by the accuracy of the temperature and wind speed measurements, and , respectively.…”
Section: Ice Surface Heat Budgetmentioning
confidence: 99%
“…Therefore, water conditions in autumn may influence the start-up of the next open water season, including the spring bloom. Previous studies have shown that ice seasons have generally become milder, resulting in a shorter duration and thinner ice cover [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of the course of ice phenomena in the local water bodies has been among the leading research topics of recent years. The researchers have attempted to characterize the icing of the water bodies of this part of Poland, especially focusing on the level of modification of ice phenomena resulting from human activity (Solarski et al, 2011;Kostecki, 2013;Rzetala, 2014;Solarski, 2017;Solarski and Rzetala, 2020). Most of the studies concerning the ice phenomena in the water bodies in the Silesian Upland and its immediate vicinity tend to focus on individual water bodies or their groupings located across small areas.…”
Section: Introductionmentioning
confidence: 99%
“…reactions of the ice to changes in air temperature (Leppäranta, 1983;Bengtsson, 1986Bengtsson, , 2012aAshton, 2011;Brown and Duguay, 2011;Kirillin et al, 2012;Yang et al, 2012;Solarski and Rzetala, 2020). The conditions for the development of ice change completely when it is covered by a thick snow cover, when the so-called isostasy of ice takes place (Ashton, 2011).…”
mentioning
confidence: 99%